Duplex Construction display booth - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows Duplex Construction display booth containing a partial wall of cinderblocks and concrete. The sign above the booth reads, "Permanent-Fire Proof, Damp Proof - Vermin Proof, Sanitary, Cool in summer, warm in winter, Duplex Construction 'It's Concrete,' Manufactured & Sold in Santa Clara Co., by F.O. Bohnett, P.O. Box 204 Campbell, The Most Economical Method of Construction." Two flower arrangements appear on pedestals at the front of the booth.